Case study: efficiency and utilization of electricity and a comparative study / Azizah Ismail - Ismail, Azizah (2004)
The main objective of this project was to compare the electrical energy efficiency and energy utilization between two hospitals namely: i. Hospital Nucleus Port Dickson (HNPD) ii. Hospital Daerah Tampin (HDT ) The two hospitals were chosen because they were built in two different eras with different set of technical and requirement standard but similar in their functions carried out. The methodology used are Physical Energy Audit and Energy Audit Data analysis, covering: i. Field observation. ii. Interview hospital staff. iii. Document review (monthly electrical bills, Engineering plant's systems operation and maintenance manual, architectural and electrical installation drawing). iv. Measurement of lights intensity. v. Reading of Ampere meter at Main Switch Board in Main Switch Room. The data was tabulated and transferred to graph and chart and analysed into chosen comparison element: i. Building Energy Index (BEI). ii. Rate of energy per bed. iii. Energy utilisation division. iv. Monthly energy consumed. v. Daily load characteristics. vi. Lighting level intensity. Through the analysis it is observed that the new standard of technical and operating requirement is affecting the energy efficiency in hospital.